2007
DOI: 10.3379/jmsjmag.31.103
|View full text |Cite
|
Sign up to set email alerts
|

Linearity Range of an Eddy Current Displacement Sensor in Relation to the Fe Film Thickness of Magnetoplated Wire

Abstract: A magnetoplated wire (MPW) is a copper wire whose circumference is plated with a magnetic thin film. The effects of using an MPW are a decrease in the proximity effect, an increase in inductance, and generation of more flux than when copper wire is used. The ratio of the linearity range Lo to the outer coil diameter D of the eddy current displacement sensor is extended by using MPW for the coil. However, the relationship between the Fe film thickness of MPWs and the linearity range characteristic has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The increase of hysteresis loss might result in the increase of the average core loss as the coating thickness increased. A similar behavior was also observed in magnetoplated wire [19]. Mizuno et al [19] studied the effect of Fe film thickness on the properties of magnetoplated wire for eddy current displacement sensor and found that among three Fe film thicknesses-i.e.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The increase of hysteresis loss might result in the increase of the average core loss as the coating thickness increased. A similar behavior was also observed in magnetoplated wire [19]. Mizuno et al [19] studied the effect of Fe film thickness on the properties of magnetoplated wire for eddy current displacement sensor and found that among three Fe film thicknesses-i.e.…”
Section: Discussionmentioning
confidence: 51%
“…A similar behavior was also observed in magnetoplated wire [19]. Mizuno et al [19] studied the effect of Fe film thickness on the properties of magnetoplated wire for eddy current displacement sensor and found that among three Fe film thicknesses-i.e. 0.7, 1, and 1.1 mm, the 1-mm film yielded the best quality factor.…”
Section: Discussionmentioning
confidence: 51%
“…Due to such structure, magnetic flux penetrating in the copper wire can be reduced, which leads to suppression of eddy currents (ECs) caused by proximity effect. Thus, the use of MPW is considered in magnetoplated (MP) coils for converters, transformers, and contactless power transfer systems as well as in EC displacement sensors …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of MPW is considered in magnetoplated (MP) coils for converters, transformers, and contactless power transfer systems [1][2][3][4] as well as in EC displacement sensors. 5 When applying finite element analysis (FEA) to electric devices, a coil must be divided into finite elements (FEs) in order to involve ECs in analysis. Particularly, skin effect and proximity effect become pronounced as driving frequency is increased, and these effects must be taken into account in element division.…”
Section: Introductionmentioning
confidence: 99%